A Special Kind of Downsizing: An Assessment of Union Member Reaction to Bumping - Stringer, Krista; Brown, Travor (Relations industrielles / Industrial Relations, 2008)
The present study investigated the impact of bumping on union member (N = 100) perceptions of job security, job satisfaction, organizational commitment, union commitment and organizational justice. Analysis revealed a negative correlation between bumping experience and organizational commitment and job satisfaction (at the .05 level). There was a similar negative relationship between bumping and both union commitment and organizational justice at the .10 level. MANCOVA found that organizational commitment and job satisfaction levels were higher for union members without bumping experience versus those with either direct or indirect bumping experience. No significant differences were found on any variable between union members who were directly involved in bumping and those who were indirectly involved.